Citraan dalam Antologi Puisi Langit Air Langit Basah karya Akhmad T Bacco - Rita Arianti; Zuriani Putri; Hermawan Hermawan; Asih Ria Ningsih; Misra Nofrita (Jurnal Bahasa dan Sastra, 2022)
The background of this research is the presence of motion imagery and auditory imagery in the poetry anthology of Langit Air Langit Basah by Akhmad T Bacco which raises the value of beauty and poetic poetry. The purpose of this study was to describe motion and auditory imagery in the anthology of the poem Langit Air Langit Basah by Akhmad T Bacco. This type of research is a qualitative research using descriptive method. This research was found 25 auditory imagery data and 36 motion data. The most dominant imagery is found in the poetry anthology Langit Air Langit Basah Akhmad T Bacco's literature is a motion image with 36 data because the themes raised in the poem are more about expressing sadness, criticism of injustice, arbitrariness, disappointment, and regret for life. Poets express all ideas, thoughts, and feelings in looking at something through words that are not clearly expressed or words that have connotations. While the imagery that was found the least was the gustatory image, which was 4 data. It can be concluded that the poet of the anthology of poetry Langit Air Langit Basah impressionism line. Impressionism is a literary genre that tries to describe a momentary impression of something the poem observes. Impressionism depicts something like a sketch, everything is not clearly depicted.